2005
DOI: 10.1159/000082396
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating plant cells switched to proliferation remodel the functional organization of nuclear domains

Abstract: The immature pollen grain, the microspore, under stress conditions can switch its developmental program towards proliferation and embryogenesis. The comparison between the gametophytic and sporophytic pathways followed by the microspore permitted us to analyse the nuclear changes in plant differentiating cells when switched to proliferation. The nucleus is highly dynamic, the architecture of its well organised functional domains – condensed chromatin, interchromatin region, nuclear bodies and nucleolus – chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 67 publications
0
42
0
Order By: Relevance
“…Numerous studies have shown a direct relationship between nuclear architecture and the level of cellular activity (Risueño and Testillano, 1994;González-Melendi et al, 1998;Testillano et al, 2000Testillano et al, , 2005Raska et al, 2004). In this work, we showed that the chromatin pattern is also affected by the induction of microspore embryogenesis in B. napus, constituting a good marker of developmental fate.…”
Section: Changes In Chromatin Pattern Parallel the Change Of Developmmentioning
confidence: 55%
“…Numerous studies have shown a direct relationship between nuclear architecture and the level of cellular activity (Risueño and Testillano, 1994;González-Melendi et al, 1998;Testillano et al, 2000Testillano et al, , 2005Raska et al, 2004). In this work, we showed that the chromatin pattern is also affected by the induction of microspore embryogenesis in B. napus, constituting a good marker of developmental fate.…”
Section: Changes In Chromatin Pattern Parallel the Change Of Developmmentioning
confidence: 55%
“…In plants, low-active nucleoli display small condensed chromatin masses, containing silent rDNA, at the nucleolar interior in the so-called heterogeneous fibrillar centers, whereas in very active nucleoli, rDNA is distributed in a decondensed state throughout the nucleolar dense fibrillar component [Risueño and Testillano, 1994;Testillano et al, 2005]. The large nucleolus of the vacuolated microspore has been characterized with a typical organization of high transcriptional activity, corresponding to the G2 phase of the cell cycle [Risueño and Testillano, 1994;González-Melendi et al, 1995;Testillano et al, 2005], the ribosomal chromatin being distributed in a decondensed state through the fibrillar component of the nucleolus, as revealed by rDNA in situ hybridization [Risueño and Testillano, 1994;Testillano et al, 2005]. In barley microspores, the nucleolus did not show 5mdC labeling, indicating a decondensed state of ribosomal chromatin which correlates with an active rDNA transcription at this developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes between chromatin states are relevant in the transcriptional regulation during microspore development and reprogramming to embryogenesis [6] and epigenetic mechanisms play an essential role in the process of cellular differentiation allowing cells to be reprogrammed in order to generate new differentiation pathways [12]. DNA methylation constitutes a prominent epigenetic modification of the chromatin fiber, which becomes locked in a transcriptionally inactive conformation, thus leading to gene silencing.…”
Section: Introductionmentioning
confidence: 99%